A Novel TAZ Gene Mutation and Mosaicism in a Polish Family with Barth Syndrome. (16th March 2015) - Zapała, Barbara; Płatek, Teresa; Wybrańska, Iwona
Summary Barth syndrome (BTHS) is an X‐linked recessive disease primarily affecting males. Clinically, the disease is characterized by hypertrophic or dilated cardiomyopathy, skeletal myopathy, chronic/cyclic neutropenia, 3‐methylglutaconic aciduria, growth retardation and respiratory chain dysfunction. It is caused by mutations in the TAZ gene coding for the tafazzin protein which is responsible for cardiolipin remodeling. In this work, we present a novel pathogenic TAZ mutation c.83T>A, p.Val28Glu, found in mosaic form in almost all female members of a Polish family. Sanger sequencing of DNA from peripheral blood and from epithelial cells showed female mosaicism in three generations. This appears to be a new mechanism of inheritance and further research is required in order to understand the mechanism of this mosaicism. We conclude that BTHS genetic testing should include two or more tissues for women that appear to be noncarriers when blood DNA is initially tested. The results of our study should not only be applicable to BTHS families, but also to families with other X‐linked diseases.